Ecosystemic Assessment of Surface Water Quality in the Virilla River: Towards Sanitation Processes in Costa Rica - Mena-Rivera, Leonardo (2018)
Water quality information is essential supporting decision making in water management processes. The lack of information restricts, at some point, the implementation of adequate sanitation, which is still scarce in developing countries. In this study, an ecosystemic water quality assessment was conducted in the Virilla river in Costa Rica, in a section of particular interest for future sanitation development. It included the monitoring of physical, chemical, microbiological and benthic macroinvertebrate parameters from 2014 to 2016. Mutivariate statistics and water quality indexes were used for data interpretation. Results indicated that water quality decreased downstream towards more urbanised areas. Particularly, extreme values of phosphorous, nitrogen and E. coli were found. Sample sites were grouped in two clusters, which were consistent with land use. Benthic macroinverterbrates diversity was predominantly represented by Baetidae, Chironomidae, Leptohyphidae, Hydropsychidae, Simuliidae and Physidae. They were mostly influenced by water temperature, nitrite, ammonium, soluble reactive phosphorous, total solids, alkalinity, nitrate and total suspended solids. Three water quality indexes consistently showed the poor condition of the water body. The overall results indicate that the main sources of pollution in the river are likely to be wastewater discharges. Thus, special efforts should be undertaken regarding its regulation in the country.